Genome-Wide Identification of JRL Genes in Moso Bamboo and Their Expression Profiles in Response to Multiple Hormones and Abiotic Stresses - Zhang, Zhijun; Huang, Bin; Chen, Jialu; Jiao, Yang; Guo, Hui; Liu, Shenkui; Ramakrishnan, Muthusamy; Qi, Guoning (Frontiers in Plant Science, 2022)
Jacalin-related lectins (JRLs) are a new subfamily of plant lectins that has recently been recognized and plays an important role in plant growth, development, and abiotic stress response. Although moso bamboo (Phyllostachys edulis) is an economically and industrially important bamboo worldwide, there has been no systematic identification of JRLs in this species. Here, we identified 25 JRL genes in moso bamboo, and these genes are unequally distributed among ten genome scaffolds. Phylogenetic analysis showed that the moso bamboo JRLs were clustered into four JRL subgroups: I, II, V, and VII. Numerous stress-responsive and hormone-regulated cis-elements were detected in the upstream promoter regions of the JRLs. Genome collinearity analyses showed that the JRL genes of moso bamboo are more closely related to those of Brachypodium distachyon than to those of O. sativa and Z. mays. Sixty-four percent of the PeJRL genes are present as segmental and tandem duplicates. qRT-PCR expression analysis showed that JRL genes in the same subgroup were significantly downregulated in response to SA, ABA, and MeJA treatments and significantly upregulated under low temperature, drought, and salt stress; they also exhibited tissue-specific expression patterns. Subcellular localization experiments revealed that PeJRL04 and PeJRL13 were localized to the cell membrane, nucleus, and cytoplasm. Three dimensional structure prediction and yeast two-hybrid assays were used to verify that PeJRL13 exists as a self-interacting homodimer in vivo. These findings provide an important foundation for understanding the functions of specific moso bamboo JRL genes and for the effective selection of stress-related genes.